Assessment of total anomalous pulmonary venous connection by two-dimensional echocardiography. - Smallhorn, J F (1981)
Twenty-three patients with total anomalous pulmonary venous connection were studied by two-dimensional echocardiography. In all cases the diagnosis was made before invasive procedures, with surgical or angiocardiographic confirmation. Eleven patients had supracardiac drainage (three to the coronary sinus, two to the right atrium,) and seven had infracardiac drainage. In the majority of cases the precise pattern of drainage could be identified by combining suprasternal, praecordial, and subcostal views. In 12 cases where the suprasternal cut was used a pulmonary venous confluence could be identified, having a cross-like structure in nine, with three others appearing as a dilated channel behind and separate from the left atrium. Thus, two-dimensional echocardiography reliably makes the diagnosis of total anomalous pulmonary venous connection and in the majority the precise pattern of drainage can be determined.